Factors influencing treatment selection and thirty-day mortality following chemotherapy for people with small cell lung cancer: an analysis of national audit data - Jones, Gavin S.; McKeever, Tricia M.; Hubbard, Richard B.; Khakwani, Aamir; Baldwin, David R. (Elsevier, 2018)
Background Thirty-day mortality after treatment for lung cancer is a measure of unsuccessful outcome and where treatment should have been avoided. Guidelines recommend offering chemotherapy to individuals with small cell lung cancer (SCLC) who have poorer performance status (PS) because of its high initial response rate. However, this comes with an increased risk of toxicity and early death. We quantified real-world 30-day mortality in SCLC following chemotherapy, established the factors associated with this and compared these to the factors that influence receipt of chemotherapy. Methods We used linked national English datasets to define the factors associated with both receiving chemotherapy and 30-day mortality following chemotherapy. Results We identified 3,715 people diagnosed with SCLC, of which 2,235 (60.2%) received chemotherapy. There were 174 (7.8%) deaths within 30 days of chemotherapy. The adjusted odds of receiving chemotherapy decreased with older age, worsening PS and increasing comorbidities. Thirty-day mortality was independently associated with poor PS (PS 2 vs PS 0 adjusted OR 3.75 95% CI 1.71-8.25) and stage (extensive vs limited adjusted OR 1.68 95% CI 1.03-2.74) but in contrast was not associated with increasing age. Both chemotherapy administration and 30-day mortality varied by hospital network. Conclusions To reduce variation in chemotherapy administration predictors of 30-day mortality could be used as an adjunct to improve sub-optimal patient selection. We have quantified 30-day mortality risk by the two independently associated factors, PS and stage, so that patients and clinicians can make better informed decisions about the potential risk of early death following chemotherapy.